Species of Megastigmidae from Morocco (Hymenoptera, Chalcidoidea) - K. Kissayi; F. Bentata; M. Labhilili; M. Ibriz (Arxius de Miscel-lània Zoològica)
Espècies de Megastigmidae del Marroc (Hymenoptera, Chalcidoidea)